Implikasi Kriteria Imkanur Rukyat Mabims Baru Terhadap Penyatuan Awal Bulan Kamariah Di Indonesia - Fitriyani, Fitriyani; Isfihani, Isfihani; Octasari, Astrie (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
The implementation of the new MABIMS criteria in 2022 stipulates that the new crescent moon can be considered visible if it has a height of at least 3 degrees and an elongation angle of at least 6.4 degrees. The change in criteria for the height of the crescent moon further distances the unification between the Government and Muhammadiyah. This research aims to analyze the implementation and impact of the implementation of the new MABIMS criteria on the unification of determining the beginning of the lunar month in Indonesia. The research uses reckoning analysis data to determine the start of Ramadan, Shawwal and Zulhijah in 1443 – 1452H. This type of research is field research. This research uses a qualitative approach. he research uses reckoning analysis data to determine the start of Ramadan, Shawwal and Zulhijah in 1443 – 1452H. This type of research is field research. This research uses a qualitative approach. The research results show that the reason for changing the MABIMS criteria was driven by astronomical considerations, namely that the shape of the crescent moon produced by the old criteria was too thin and easily obscured by twilight light. Then, the implementation of the new MABIMS criteria resulted in a greater difference in the criteria for crescent height, namely 0 to less than 3 degrees. Data on calculating the height of the hilal from 1443 AH - 1452 AH shows that there were 13 times the height of the hilal which did not meet the criteria for the new Imkanur Rukyat MABIMS but met the criteria for the shape of the hilal. [Penerapan kriteria MABIMS yang baru pada tahun 2022 menetapkan bahwa hilal baru dapat dianggap terlihat jika memiliki ketinggian minimal 3 derajat dan sudut elongasi minimal 6,4 derajat. Perubahan kriteria tinggi hilal justru semakin menjauhkan adanya penyatuan antara Pemerintah dengan Muhammadiyah. Penelitian ini bertujuan menganalisis implementasi dan dampak implementasi kriteria MABIMS baru terhadap penyatuan penentuan awal bulan Kamariah di Indonesia. Penelitian menggunakan data analisis hisab penentuan awal Ramadan, Syawal dan Zulhijah tahun 1443 – 1452H. Jenis penelitian ini adalah field research. Penelitian ini yang menggunakan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa alasan perubahan kriteria MABIMS didorong oleh pertimbangan astronomis, yaitu bentuk hilal yang dihasilkan oleh kriteria lama terlalu tipis dan mudah terhalang oleh cahaya senja. Kemudian, implementasi kriteria MABIMS baru mengakibatkan selisih kriteria tinggi hilal lebih besar yakni 0 hingga kurang 3 derajat. Data hisab tinggi hilal dari tahun 1443 H- 1452 H menunjukkan bahwa terdapat 13 kali tinggi hilal yang tidak memenuhi kriteria Imkanur Rukyat MABIMS baru namun memenuhi kriteria wujudul hilal].